2012
DOI: 10.1002/jcp.23005
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose‐induced repression of RAR/RXR in cardiomyocytes is mediated through oxidative stress/JNK signaling

Abstract: The biological actions of retinoids are mediated by nuclear retinoic acid receptors (RARs) and retinoid × receptors (RXRs). We have recently reported that decreased expression of RARα and RXRα has an important role in high glucose (HG)-induced cardiomyocyte apoptosis. However, the regulatory mechanisms of HG effects on RARα and RXRα remain unclear. Using neonatal cardiomyocytes, we found that ligand-induced promoter activity of RAR and RXR was significantly suppressed by HG. HG promoted protein destabilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 61 publications
3
39
3
Order By: Relevance
“…Although high glucose presently did not increase IGFBP5 protein levels in cardiomyocytes, the IGFBP5 released from cardiac fibroblasts may promote the apoptosis of cardiac myocytes. The IGFBP5-mediated increase in JNK phosphorylation observed in our study also supports a proapoptotic effect of IGFBP5, as JNK is involved in high glucose-induced apoptosis in cardiomyocytes (Kuo et al 2012, Singh et al 2012. JNK may mediate IGFBP5-induced apoptosis in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 85%
“…Although high glucose presently did not increase IGFBP5 protein levels in cardiomyocytes, the IGFBP5 released from cardiac fibroblasts may promote the apoptosis of cardiac myocytes. The IGFBP5-mediated increase in JNK phosphorylation observed in our study also supports a proapoptotic effect of IGFBP5, as JNK is involved in high glucose-induced apoptosis in cardiomyocytes (Kuo et al 2012, Singh et al 2012. JNK may mediate IGFBP5-induced apoptosis in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 85%
“…This pathway also involved ROS, c-JUN N-terminal kinase (JNK), and a peroxisome proliferator-activated receptor g, coactivator 1 a (PGC1a) and contributed to the decrease in mRNA abundances of nuclear-encoded OXPHOS enzymes, which would further aggravate OXPHOS dysfunction caused by the mt3243 mutation. Although the negative regulation of RXRA abundance through JNK activated by ROS (11) and the interaction between RXRA and PGC1a (12) have been previously reported, the connection of this pathway to mitochondrial retrograde signaling has not. Here, we demonstrated that (i) mitochondrial dysfunctions decreased RXRA abundance, (ii) the reduction in RXRA decreased the interaction between RXRA and PGC1a, (iii) the reduced interaction contributed to the decrease in mRNA abundances of OXPHOS and translation-related genes, and (iv) the reduction of OXPHOS and translation-related genes was reversed by the addition of retinoic acid (RA).…”
Section: Introductionmentioning
confidence: 95%
“…RXRα/RAR heterodimers play a role in the retinoid-stimulated increase in steroid sulfatase activity which was blocked by pharmacological inhibition of the RAF-1 and ERK MAP kinases [52]. Accumulating evidence that ligand-induced promoter activity of RXRα/RAR heterodimer is significantly suppressed by high glucose (HG) which promoted protein destabilization and serine-phosphorylation of RAR and RXR is mediated through oxidative stress/JNK signaling [53]. The impaired RXRα/RAR signaling and oxidative stress/JNK pathway forms a vicious circle, which significantly contributes to cardiomyocyte apoptosis induced by hyperglycemia [53].…”
Section: Therapeutic Applications Of Rar/rxr Heterodimer Modulators Imentioning
confidence: 99%
“…Accumulating evidence that ligand-induced promoter activity of RXRα/RAR heterodimer is significantly suppressed by high glucose (HG) which promoted protein destabilization and serine-phosphorylation of RAR and RXR is mediated through oxidative stress/JNK signaling [53]. The impaired RXRα/RAR signaling and oxidative stress/JNK pathway forms a vicious circle, which significantly contributes to cardiomyocyte apoptosis induced by hyperglycemia [53]. The RXRα/RAR signaling pathway plays critical roles in hippocampal synaptic plasticity and greatly contributes to memory performance, and long-term potentiation (LTP) in the hippocampus in the adult brain [54].…”
Section: Therapeutic Applications Of Rar/rxr Heterodimer Modulators Imentioning
confidence: 99%